Efektivitas Penggunaan Model Cooperative Script Berbantuan Flash card Terhadap Kemampuan Berbicara Bahasa Indonesia Peserta Didik Kelas III - Lisa Rosdayanti; Chairul Amriyah; Yuli Yanti (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the effect of the Cooperative Script learning model assisted by flashcard media on elementary students’ speaking skills. This research employed a quantitative approach with a quasi-experimental design, specifically a posttest-only control group design. The sample consisted of two groups, namely the experimental class and the control class, using saturated sampling technique, in which all members of the population were included as research subjects. The research instrument was a speaking test based on indicators of fluency, pronunciation, vocabulary, grammar, and comprehension. Data were analyzed using t-test and effect size. The results showed that the average speaking ability of students in the experimental class was higher than that of the control class. Furthermore, hypothesis testing indicated a significant difference between the two groups, with the effect size categorized as moderate to high. These findings suggest that the Cooperative Script model assisted by flashcards is effective in improving students’ speaking skills. This study implies that the integration of cooperative learning models with visual media can be an effective strategy in teaching Bahasa Indonesia at the elementary level.